Interleukin 25 (IL-25) expression in cholangiocarcinoma - Kaewsarabhumi, Supakit (Mol Clin Oncol, 2020)
Various cytokines are involved in carcinogenesis and tumor progression. Some tumor cells produce cytokines by themselves. Using secretome analysis, a high expression of APEX-1 was found in cholangiocarcinoma (CCA) cell lines. During this secretome analysis, it was found that CCA cell lines overexpressed some cytokines and related molecules, including interleukin 25 (IL-25). In the present study, we first performed precise secretome analysis on cytokines and related molecules in CCA cell lines and identified that IL-25 was overexpressed in CCA cell lines. Then, using immunohistochemical methods, we investigated the expression of IL-25 in the cancer tissues from 20 CCA patients in Northeast Thailand. Correlation between IL-25 expression levels and patients' clinical parameters were analyzed. The results showed that IL-25 expression was significantly (P<0.0001) higher in cancerous tissues than in the normal bile ducts and in the adjacent tissues. Overexpression of IL-25 protein in CCA tissue was confirmed using western blot analysis. Moreover, IL-25 expression in cancerous tissues was significantly (P<0.0015) higher in CCA patients with metastasis than in CCA patients without metastasis. Survival analysis revealed that a high expression of IL-25 was correlated with shorter survival time of CCA patients (P=0.0260). Aberrant expression of IL-25 in CCA tissue was associated with tumor metastasis and poor prognosis, suggesting that IL-25 is a potential prognostic biomarker. Biological roles of IL-25 in CCA genesis and progression should be explored in future.